Antibodies in acquired demyelinating disorders in children. Issue 1 (December 2016) - Armangue, Thaís; Yeshokumar, Anusha; Sepúlveda, Maria; Graus, Francesc; Saiz, Albert
Abstract The discovery that several demyelinating disorders in children may be associated with autoantibodies to astrocytes, myelin, and/or synaptic proteins has opened the possibility of their use as diagnostic and prognostic biomarkers. The identification of aquaporin 4 (AQP4) antibodies as specific diagnostic markers of neuromyelitis optica (NMO) led to an expansion of the clinical spectrum of this disorder to include patients with incomplete forms or with manifestations outside of the optic nerves and spinal cord. Recently, an international panel of experts proposed the use of the term NMO spectrum disorders (NMOSD) to encompass all of these phenotypes. Although rare in children, the early identification of AQP4 antibodies has important prognostic and therapeutic implications as their presence is highly predictive of relapses and accumulation of disability. More recently, antibodies to myelin oligodendrocyte glycoprotein (MOG) have been described in children and adults diagnosed with NMOSD and seronegative for AQP4 antibodies, as well as in children with other acquired demyelinating disorders. For example 60 % of children with acute demyelinating encephalomyelitis (ADEM) have MOG antibodies. Whether MOG antibodies are pathogenic or surrogate biomarkers of the disease is unclear but their identification is important for two reasons. First, patients with a first demyelinating event who are MOG antibody positive are unlikely to develop multiple sclerosis (MS); and second, the long-term persistence of MOG antibodies associates with recurrent non-MS demyelinating disorders such as NMOSD, recurrent optic neuritis or transverse myelitis, or multiphasic ADEM. Other antibodies, such as those targeting Kir 4.1 or the glycine receptor have also been described in association with pediatric MS and other demyelinating disorders but their clinical relevance, and existence, in the case of Kir 4.1, is still under investigation. The focus of this review will be the current data on the antibodies mentioned above, and the recent discovery that some children have both a demyelinating disorder and autoimmune encephalitis. The presence of antibodies against targets related to demyelinating disorders (AQP4 or MOG) and those related to autoimmune encephalitis (e.g., N-methyl-D-aspartate receptor), supports the concurrence of two autoimmune disorders in these patients.